A Path Out: Using Video Games to Reduce Prejudice Towards Refugees - Liam Cross; Gray Atherton; Chris Stiff (Behavioral Sciences)
Historically, research on video games has centred on their potentially adverse effects, though more recently, work has started to explore the benefits. Here, we investigate whether playing a video game portraying a refugee’s plight in escaping war-torn Syria could affect implicit and explicit attitudes towards that social group. We show that after 30 min of game play embodying a Syrian refugee, participants showed reduced prejudicial attitudes and increased empathy towards Syrian refugees compared to those playing a mechanically similar but contextually unrelated game. While implicit attitudes followed the same direction, this difference was not statistically significant. Potential theoretical underpinnings of these findings, including perspective taking, embodiment, and contact perspectives for prejudice reduction, are discussed.